A Review of Research Outcomes on Fabrication Methods and Investigations for Evaluating Fracture Behavior of Aluminum Metal Matrix Composites with its Applications - Chandran Gururaj; Pandian Pitchipoo; Sivaprakasam Rajakarunakaran (Mechanics of Advanced Composite Structures)
Metal matrix composites are widely used in engineering applications because of their better mechanical properties. This review focuses on fabrication methods and fracture behaviors of aluminum metal matrix composites (AMMCs). This paper also discusses its applications. Based on the review study, it is observed that the properties of AMMC vary depending on the reinforcement used, fabrication techniques, and reinforcement disbursement in the matrix material. It is also found that the place where the composite materials are used and the difficulties behind the manufacturing processes decide the selection of reinforcements and the types of fabrication method. It is noticed that the reinforcement of AMMCs is in the form of continuous fibers, short fibers, whiskers, and particulates. The objective of this review study is to summarize the details about the techniques used for fabricating aluminum metal matrix composites, the effects of processing parameters on the mechanical behaviors of composites, the different types of test specimens, and the fixtures used to apply load for fractures experimentations of AMMC with the applications of AMMCs in various fields.